Functional and structural pattern of arterial responses in hereditary hypertriglyceridemic and spontaneously hypertensive rats in early stage of experimental hypertension - Török, J; Koprdová, R; Cebová, M; Kunes, J; Kristek, F (Physiological research, 2006)
It has been shown that endothelium-derived nitric oxide (NO) plays an important role in regulation of vascular tone in the prenatal and early postnatal period. The aim of this paper was to determine the reactivity and accompanying structural changes in thoracic aorta from 4-week-old spontaneously hypertensive rats (SHR) and rats with hereditary hypertriglyceridemia (hHTG) in comparison with age-matched normotensive controls. For functional studies thoracic aorta was excised, cut into rings and mounted in organ baths for measurement of isometric contractile force. For morphological studies cardiovascular system of rats was perfused with glutaraldehyde fixative (at 100 mm Hg) via cannula placed in the left ventricle. Morphological changes of thoracic aorta were measured using light microscopy. Systolic blood pressure (SBP) in SHR (98+/-1 mm Hg) did not significantly differ from that of age-matched control rats (95+/-4 mm Hg), but was slightly increased in hHTG rats (110+/-2 mm Hg, P<0.05). Heart weight/body weight ratio was higher in SHR and hHTG rats than in control group indicating the hypertrophy of the heart in both models of hypertension. Endothelium-dependent relaxation of aorta induced by acetylcholine was preserved in all groups and did not differ from that in control normotensive rats. The maximal isometric contraction of thoracic aorta to noradrenaline (NA) was reduced in hypertensive groups and the concentration-response curves to NA were shifted to the right indicating increased sensitivity of smooth muscle to NA. The values of wall thickness and cross sectional area as well as inner diameter of thoracic aorta in SHR and hHTG rats were significantly decreased in comparison to control groups. Endothelial dysfunction seems to be absent in all young rats before development of hypertension. In conclusion, our observations indicate that in early stage of experimental hypertension NO-dependent relaxation is preserved so that putative impairment of this function provides no significant pathogenic contribution to the onset of hypertension in these two experimental models.
Keywords: hypertriglyceridemie; Aorta, Thoracic; Endothelium, Vascular; Hypertension; cévní endotel; oxid dusnatý; krysa rodu Rattus; zvířata; Nitric Oxide; Norepinephrine; potkani Wistar; Hypertriglyceridemia; aorta thoracica; Rats, Wistar; Male; potkani inbrední SHR; hypertenze; Rats; noradrenalin; Animals; mužské pohlaví; Rats, Inbred SHR